Synthesis of halogen-substituted styryl lactones and their cytotoxic activity against T-jurkat cell line / Nik Salmah Nik Salleh - Nik Salleh, Nik Salmah (2014)
Styryl lactones are small organic compounds that possess interesting biological properties. A study was done in order to synthesise halogen substituted styryl lactones as only few of these derivatives have been reported. A new synthetic route has been established which consists of three steps only. Commercially available 3,4-dihydro-2//-pyran-2-methanol was used as starting material and subjected to Swem oxidation to provide the corresponding aldehyde. This reaction was conducted at -78 °C in the presence of dimethyl sulfoxide (DMSO), oxalyl chloride (COCl)2 and triethylamine (EtjN). Phosphonium salts were synthesised through microwave irradiation. These phosphonium salts were subjected to a base to yield Wittig reagents. Wittig reactions were performed in a -40 °C bath by using tetrahydrofuran (THF) and sodium bis(trimethylsilyl)amide (NaHMDS) leading to (Z)-precursors of halogensubstituted styryl lactones. The oxidation of the styryl lactone precursors with tert-butyl hydroperoxide (/buBOOH) and pyridinium dichromate (PDC) in dichloromethane (CH2CI2) at -40 °C yielded the targeted products as well as two by-products with overall yields of main product ranging from 45 % to 67 %. The final products were purified by both column chromatography and preparative layer chromatography (PLC). The structures of the synthesised compounds were confirmed by nuclear magnetic resonance (NMR) and mass spectrometry analyses. The cytotoxic activity of the six final compounds was tested on E6.1 Jurkat-T cell line. All targeted compounds showed encouraging cytotoxic activity with IC50 ranging from 26 % to 120 % of that goniothalamin.